Pengembangan Presensee: Aplikasi Presensi Mahasiswa Mobile Menggunakan Framework Flutter (Studi Kasus: Studi Independen Alterra Academy - Alief Iksan Al Ghani; Rian Andrian (Jurnal Media Infotama, 2023)
The Presensee is a student’s online presence application developed on a mobile platform. The purpose of developing this application is to overcome some of the problems of conventional attendance methods, including limitations in terms of efficiency and accuracy. The manual attendance method using paper or attendance cards tends to be time-consuming, prone to fraud, and difficult to process. The present study was developed using the Flutter framework in the Dart language. Flutter was chosen because it is a universal platform in which only one program is needed for one application on all types of platforms. Be it Android, iOS, Web, or Desktop.